UPAYA PENINGKATAN PENGETAHUAN KEPADA MASYARAKAT TERHADAP DAGUSIBU (DAPATKAN, GUNAKAN, SIMPAN, BUANG) OBAT - Neneng Sri Purwaningsih; Beny Maulana Satria; Bheta Sari Dewi; Suny Koswara Rahajeng; Aulia Nadya Rizki Imansari; Anis Dwi Kristiyowati; Firdha Senja Maelaningsih (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
One of the drug-related problems that is still widely found in society is drug abuse. Drug abuse that often occurs includes discovery of counterfeit drugs, drug trafficking, and the use of other dangerous substances. This happens because one of the factors is a lack of knowledge regarding drug management. Good drug management can be implemented through Dagusibu (Get, Use, Store, Dispose) Drugs. Therefore, it is necessary to provide community service in the form of Dagusibu Drug education to the community. The method used in this community service activity is the participatory community empowerment method with the Partipatory Rural Appreciation (PRA) model, which emphasizes community involvement in all activities carried out with direct outreach techniques to the community. The aim of this activity is to provide information and increase knowledge about Dagusibu Medicine to the community on Jl. Bakti Jaya Luk, Bakti Jaya Village, Setu District, South Tangerang City. Community service was carried out on May 8, 2024, and was attended by 23 participants. The result of this community service activity was an increase in public knowledge Obtaining, Using, Storing, and Disposing of (Dagusibu) medicines correctly, so that rational use of medicines will be realized and there will be no drug abuse.